Reading Skills Through Active Reading Techniques - Djabbarova Dilfuza G’ayratovna (Zien Journals, 2022)
The aim of this article, thus, is to outline about reasons for using reading rexts in class, kinds of reading texts that are suitable for English language students, types of written language, types of classroom reading performance and examples of reading materials.
Keywords: Reading performance; written language; reading materials; communicative tasks